2019
DOI: 10.1097/md.0000000000016267
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte/lymphocyte ratio is related to the severity of coronary artery disease and clinical outcome in patients with non-ST-elevation myocardial infarction

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 37 publications
4
87
0
3
Order By: Relevance
“…In this meta-analysis, we enrolled 5 studies comprising 4343 patients to investigate the prognostic value of the LMR in patients with ACS [18,[21][22][23][24]. The present study showed that LMR might be a predictor for short-term mortality/MACE.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In this meta-analysis, we enrolled 5 studies comprising 4343 patients to investigate the prognostic value of the LMR in patients with ACS [18,[21][22][23][24]. The present study showed that LMR might be a predictor for short-term mortality/MACE.…”
Section: Discussionmentioning
confidence: 70%
“…The result showed that LMR predicted short-term mortality/MACE (HR = 3.44, 95% CI: 1.46-8.14, P < 0.05, Figure 2A), with low levels of heterogeneity among studies (I 2 = 0%). The combined analysis of 5 studies covering 4343 patients described the relationship between LMR and longterm mortality/MACE [18,[21][22][23][24]. The pooled outcome for low LMR value compared with high LMR value group was found to be 1.70 (95% CI: 1.36-2.13, P < 0.05, Figure 2B), with moderate levels of heterogeneity among studies (I 2 = 46.8%).…”
Section: Lmr and Mortality/macementioning
confidence: 95%
See 1 more Smart Citation
“…[ 4 , 5 ] Recently, Hanhua et al reported that monocyte-to-lymphocyte ratio (MLR) was an independent risk factor of the presence of CAD, and significantly associated with coronary lesion severity. [ 6 , 7 ] Furthermore, Chen et al reported that MLR was an independent predictor for major adverse cardiovascular event in patients with non-ST segment elevated myocardial infarction. [ 7 ] It was also demonstrated that increased MLR level was associated with higher morality in patients with acute heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hanhua Ji, et al reported that monocyte-to-lymphocyte ratio (MLR) was an independent risk factor of the presence of CAD, and significantly associated with coronary lesion severity [6,7] . Furthermore, Chen H, et al reported that MLR was an independent predictor for major adverse cardiovascular event (MACE) in patients with non-ST segment elevated myocardial infarction (NSTEMI) [7] .It was also demonstrated that increased MLR level was associated with higher morality in patients with acute heart failure [8] . However, the relationship between the MLR level and plaque vulnerability has not been sufficiently evaluated.…”
Section: Introductionmentioning
confidence: 99%